Anticomunismo nas forças armadas: um estudo de caso à partir de monografias da Escola de Comando e Estado-Maior do exército - Alves, Rodrigo Souza (Universidade Federal de São Carlos, 2023)
In an interview with BandNews TV on January 31, 2023, Defense Minister José Múcio Monteiro stated that he will “have to negotiate” the end of the March 31 celebrations. These celebrations make reference to a shameful moment in the history of our country: the date of the deposition of President João Goulart, which began the 1964 coup d'état, a conspiracy involving civilians and the military to overthrow the current government, with the justification of combating a communist infiltration in our homeland and guided by the anticommunist imaginary rooted in Brazilian society since 1930. Based on this context, this course conclusion work aimed to analyze the relationship between the military - in particular the members of the Brazilian Army - and the set of anticommunist ideas used by the right recently in Brazil. To achieve this objective, a general definition of what is understood as anticommunism was made in conjunction with a discussion about the historical relationship of anticommunist ideas with the Brazilian Armed Forces and the transformation of this ideology today. At the end of this research, an analysis of two monographs of officers trained at ECEME in 2019 was carried out, demonstrating the influence of anticommunist ideology on the main step in the process of training Army officers to one day reach the generalship, where it was possible to identify that anticommunism still fulfills in the imagination of the military the role of legitimizing their possible interventions in civil society.
Anticommunism in the armed forces: a case study based on monographs from the Escola de Comando e Estado-Maior do exército
Keywords: Exército Brasileiro; Anticomunismo; ECEME; Olavo de Carvalho; Sérgio Avellar Coutinho; CIENCIAS HUMANAS::ANTROPOLOGIA